2015
DOI: 10.1128/ec.00241-14
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Sarcolemmal Membrane-Associated Protein (SLMAP) Homolog Plays a Fundamental Role in Development and Localizes to the Nuclear Envelope, Endoplasmic Reticulum, and Mitochondria

Abstract: bSarcolemmal membrane-associated protein (SLMAP) is a tail-anchored protein involved in fundamental cellular processes, such as myoblast fusion, cell cycle progression, and chromosomal inheritance. Further, SLMAP misexpression is associated with endothelial dysfunctions in diabetes and cancer. SLMAP is part of the conserved striatin-interacting phosphatase and kinase (STRIPAK) complex required for specific signaling pathways in yeasts, filamentous fungi, insects, and mammals. In filamentous fungi, STRIPAK was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
122
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(131 citation statements)
references
References 75 publications
7
122
0
Order By: Relevance
“…The essential role of these factors in anastomosis formation was first described for S. macrospora and N. crassa and has also been confirmed in the plant pathogenic species Colletotrichum graminicola [54,[57][58][59][60][61]. STRIPAK functions are complex, especially because its core can associate and interact with various other proteins, and individual factors of the complex can possess STRIPAK-independent roles.…”
Section: Stripakmentioning
confidence: 87%
See 1 more Smart Citation
“…The essential role of these factors in anastomosis formation was first described for S. macrospora and N. crassa and has also been confirmed in the plant pathogenic species Colletotrichum graminicola [54,[57][58][59][60][61]. STRIPAK functions are complex, especially because its core can associate and interact with various other proteins, and individual factors of the complex can possess STRIPAK-independent roles.…”
Section: Stripakmentioning
confidence: 87%
“…Consistent with their various tasks, STRIPAK factors localize to different subcellular regions and organelles. In S. macrospora and N. crassa, the STRIPAK complex is associated with the nuclear envelope, where it might interact with the MAP kinase signaling network [54,60]. The phocein MOB-3 is phosphorylated by MAK-2, and this phosphorylation controls nuclear entry of the MAK-1 kinase, indicating the close integration of these different signaling hubs [54].…”
Section: Stripakmentioning
confidence: 99%
“…In previous studies, many factors required for the development of fruiting bodies have been identified in S. macrospora (Kück et al, ; Teichert et al, ). Among these factors, the multiprotein complex striatin‐interacting phosphatase and kinase complex (STRIPAK) (Kück et al, ) has gained significant interest beyond fungal development because its components are conserved from yeasts to mammals (Table ) (Xiang et al, ; Pöggeler and Kück, ; Shim et al, ; Goudreault et al, ; Maerz et al, ; Bloemendal et al, ; Engh et al, ; Simonin et al, ; Wang et al, ; Bernhards and Pöggeler, ; Bloemendal et al, ; Santarpia et al, ; Dettmann et al, ; Nordzieke et al, ; Beier et al, ; Green et al, ; Kück et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Human STRIPAK complex includes: PP2Ac: Protein phosphatase 2 A catalytic subunit, PP2AA: Protein phosphatase 2 A scaffolding subunit A, MOB3: Monopolar spindle one binder 3, CCM3: Cerebral cavernous malformation 3, STRIP1/2: Striatin interacting proteins 1 and 2, GCK III: Germinal center kinase III family of Ste20 kinases, CTTNBP2/CTTNBP2NL: Cortactinbinding protein 2, SLMAP: Sarcolemmal membrane‐associated protein, TRAF3IP3: Tumor necrosis factor receptor‐associated factor 3 interacting protein 3, SIKE: Suppressor of IKKε, and FGFR1OP2: Fibroblast growth factor receptor oncogene partner 2. a Identified in this study with BLASTP as SCI1 homolog, b identified in this study. In S. macrospora orthologs of the STRIPAK complex, but not SCI1 were identified and characterized by Beier et al (), Bernhards and Pöggeler (), Bloemendal et al (), Bloemendal et al (), Nordzieke et al (), Pöggeler and Kück () and Kück et al ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation